The interaction between renewable energy consumption and the institutional framework from a circular economy-based perspective - Adriana Florina Popa; Valentin Burcă; Daniela Nicoleta Sahlian; Daniela Livia Trască (Amfiteatru Economic Journal, 2022)
The European Green Deal describes the vision and strategic orientation of EU members of future public policies, which is designed to harmonize countries' efforts to align national economies with the principles of the circular economy. Among the directions prescribed by the European Green Deal, we find an increase of renewable energy (RE) consumption in parallel with improving energy efficiency and reducing the energy sources that involve significant negative environmental impact in the long run. Our study addressed the association between RE consumption, management decision-making factor, policy landscape addressing energy efficiency, and sustainability innovation capabilities, at a firm-level analysis. For this purpose, we assess the causality between these variables, performing a time series analysis on a sample that covers the period between 2011 and 2019. Regression models are estimated with panel time series FMOLS (Fully Modified Ordinary Least Squares) and DMOLS (Dynamic Modified Ordinary Least Squares) estimation methods. The results underscore that the evolution of renewable energy consumption by firms depends on the management decision, related both to the commitment of managers to sustainable strategies and the effectiveness of governance processes. Nonetheless, our results emphasize the essential role of the country's institutional factor, which should ensure proper regulation, effective enforcement mechanisms, and financial incentives that promote the RE usage.
Keywords: M14; Q01; Q42; Q56; O13; 330; circular economy; energy efficiency; Fully Modified Ordinary Least Squares; generalized method of moments.; regulatory indicators for sustainable energy; renewable energy